Playing the Isothymia Ethnic Card on Harmony: Malaysia’s Current State. - Mohd Nizah, Mohd Azmir; Abu Bakar, Afi Roshezry (Journal of Islamic, Social, Economics and Development, 2025)
Malaysia’s rich cultural mosaic comprises various ethnic groups, with Malays, Chinese, Indigenous Sabah and Sarawak, and Indians being the predominant communities. This diversity has been central to Malaysia’s national identity, yet it has also presented challenges in fostering genuine social cohesion. Central to this discourse is “isothymia,” referring to the universal human desire for equal recognition and respect. This paper will analyze the trend of the interplay between ethnic identity and the pursuit of isothymia, which has profound implications for national harmony. This paper uses a qualitative design with a content analysis method to argue that the current isothymiatic syndrome is rising despite government social reformation efforts. It is pertinent to recognize and address the isothymiatic aspirations of all ethnic groups, which is crucial for Malaysia to foster genuine unity and social cohesion